Akut prostatit hos hund : en retrospektiv studie av ultraljudsbilden på 15 hundar med kliniska tecken på akut prostatit - Mattsson, Johanna (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2006)
Acute bacterial prostatitis is a common disease in older male dogs. It gives symptoms such as fever, pain, tiredness, infertility, unwillingness to mate and sometimes symptoms from the urinary tract. It is common that you do an ultrasound exam on dogs when you suspect prostatic changes.